The Gendered Psyche of Emotional Labor: A Psychological Exploration of Expectation, Performance, and Burnout in the Digital Era - Xiao, Yayun (Simen Owen Academic Proceedings Series, 2025)
Emotional labor has long been recognized as central to service economies, yet the digital era amplifies its psychological dimensions through algorithmic monitoring, constant connectivity, and gendered cultural expectations. While prior research has extensively explored the sociological and organizational facets of emotional labor, comparatively little attention has focused on the psychological mechanisms linking expectations, performance, and burnout in digitally mediated work. To address this gap, this study integrates emotional labor theory, gender role perspectives, and burnout models into a unified analytical framework. Methodologically, it adopts a qualitative, interdisciplinary approach combining recent literature review, textual and discourse analysis, and comparative case studies of Amazon digital customer service representatives, post-pandemic remote teachers, and social media influencers. Findings indicate that women encounter heightened and gender-specific emotional demands: customer service workers are pressured to over-perform scripted friendliness, remote teachers engage in deep acting under conditions of role overload, and influencers navigate hybrid authenticity performances that merge personal identity with brand expectations. These dynamics contribute to diverse yet convergent forms of burnout, disproportionately affecting women. By extending emotional labor models into digital contexts, this study advances theoretical understanding and offers practical guidance for designing equitable workplace policies, establishing digital boundaries, and enhancing platform accountability.